THE ROLE OF THE TERRITORIAL COMMUNITY DEVELOPMENT STRATEGY IN THE CREATION OF COMPREHENSIVE TERRITORIAL COMMUNITY DEVELOPMENT PLANS (ON THE EXAMPLE OF THE ZHYDACHIV TOWN TERRITORIAL COMMUNITY OF STRYI DISTRICT, LVIV REGION) - Pyrih А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The development strategy of the Zhydachiv territorial community and its role in creating a comprehensive development plan for the territory of the Zhydachiv TTC were studied. The main provisions of the Development Strategy are reflected in the study, which is a document of strategic planning at the local level. The territorial community development strategy is a document of strategic planning at the local level, which defines strategic, operational goals and objectives for the sustainable development of the territorial community, developed for the period of implementation of the State Regional Development Strategy and the corresponding regional development strategy until 2027. The administrative-territorial structure of Zhydachiv TTC is reflected, an analysis of community lands is given, potential areas of implementation of the operational goal "Territory development planning" provided for by the Strategy of Zhydachiv TTC are analyzed, the main problems that are not reflected in the Development Strategy and ways to solve them are outlined. It is proposed to solve the problems related to the functioning of the city landfill with regard to the reduction of solid household waste, in particular by adopting the experience of France; using the lands of the Zhydachiv Pulp and Paper Plant; the functioning of the community's water bodies, in particular the main water artery - the Stryi River, and the effective use of coastal protective strips of water bodies;lack of cultural and recreational facilities; functioning of premises of institutions that are not in use; creation and functioning of the association of co-owners of apartment buildings; creation of additional tourist routes.